Global strategy collections: Emerging market multinational enterprises. (9th April 2022) - Pedersen, Torben; Tallman, Stephen
Abstract: Research Summary: This first collection of articles for global strategy focuses on the relatively new phenomenon of Emerging Market Multinational Enterprises (EMNEs). The first topic to draw real attention to articles in Global Strategy Journal, the study of EMNEs challenges many assumptions about what characteristics make a firm a successful MNE and forces a reconsideration of fundamental questions in strategic management. The articles in the collection provide a good introduction to the topic, but there is much more research on the topic in a variety of journals for those scholars considering the EMNE as a topic for their own research. Managerial summary: In the last couple of decades, we have seen the emergence of EMNEs that are competing globally. This primer on EMNEs points at the specificities of EMNEs including their ownership‐specific advantages, their pattern of internationalization, their innovation strategies for catching‐up, and not least how their ownership and the home conditions in less developed countries alter their behavior. These are important factors that serve to help scholars to understand the strategies and actions of EMNEs and how they gain their competitive strengths on the global scene.